AI Chatbots for Personalized Grammar Feedback and Autonomous Learning to Improve Accuracy, Engagement, and Writing Skills - Afriana Afriana; Sipri Hanus Tewarat; Tomas G. Belano (Global Education : International Journal of Educational Sciences and Languages, 2025)
Grammar correction has long been recognized as one of the most essential yet challenging aspects of second language (L2) learning. Teachers are expected to provide detailed and contextual feedback, but this process is often time-consuming and less effective in large classrooms. This study investigates the potential of AI-based chatbots as innovative tools for delivering personalized and real-time grammar feedback to support English language learning. The research employed an experimental design involving two groups: an experimental group using AI chatbots for grammar practice and a control group applying traditional teacher-based correction. Data were collected through grammar pre-tests and post-tests, writing tasks, engagement and motivation questionnaires, classroom observations, and student reflection notes. The findings demonstrate that students in the experimental group achieved significantly higher improvements in grammar accuracy compared to the control group, particularly in subject–verb agreement, tense usage, and complex sentence structures. In addition, chatbot use fostered greater engagement, motivation, and active participation, with students reporting reduced language anxiety and increased confidence in practicing English. Writing performance also improved, as students in the experimental group produced more structured, coherent, and grammatically varied texts. These results highlight the potential of AI chatbots not only to enhance linguistic accuracy but also to promote autonomous and personalized learning. In conclusion, AI chatbots represent an effective and scalable pedagogical tool that can complement traditional teaching methods while addressing teachers’ time constraints and improving students’ overall language learning outcomes.